Facile synthesis and electrochemical performance of bacterial cellulose/reduced graphene oxide/NiCo-layered double hydroxide composite film for self-standing supercapacitor electrode - Saputra, A. Muhammad Afdhal (2024)
This study employs a cost-efficient method to create a pliable BC/rGO-NiCo-LDH electrode film on a bacterial cellulose base. X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX) analyses verified the incorporation of reduced graphene oxide (rGO) and nickel–cobalt layered double hydroxide (NiCo-LDH) into the bacterial cellulose structure. The BC/rGO-NiCo-LDH composite material exhibited high-temperature stability and achieved a specific capacitance of 311 F g−1 at a scan rate of 0.1 mV/s, surpassing that of earlier cellulose electrodes. The electrode film showed exceptional mechanical capabilities, displaying flexibility and load resistance without any structural damage. The film's flexibility and lightweight properties were improved due to the low density of 0.656 g cm−3, which is a result of the nanoporous structure and intrinsic low density of rGO and cellulose. A retention ratio of 0.40 for storage modulus at a glass transition temperature of around 90°C demonstrated positive mechanical performance. This cost-effective and uncomplicated synthesis approach produced a BC/rGO-NiCo-LDH electrode with potential. The material possessed favourable mechanical and electrochemical characteristics, making it suitable for wearable electronics.